A Decision Support System for Programme Design Based on Learning Units - Abdul-Aziz, Azlianor; Meziane, Farid (2004)
A module is the basic component in the education field. It is created based on a set of criteria and requirements that are clearly defined. Occasionally, modules generated manually could cause overlapping between modules where a large part of one module is taught in another one. This may then raise the question of whether the right knowledge is transmitted to students and whether the learning outcomes are met. In this paper, we describe a Decision Support System (DSS) that helps in the design and development of module content to avoid overlapping between modules and checks consistency of modules contents with regards to a specific body of knowledge. This will guarantee that most, if not all the knowledge described in the knowledge body is covered in a set of modules designed for a specific programme. In addition, modules are created based on predefined learning units and a set of constraints. Topics are divided into smaller units with clearly defined attributes for efficiency and effectiveness of module design. The constraints associated with learning units include pre-requisite, learning outcomes aims and objectives and required learning time.